Izkušnje pri načrtovanju in razvoju storitvene arhitekture - Tekavc, Marko (Uporabna informatika (Ljubljana), 2006)
Service oriented architecture ISOAJ is currently a very popular topic. Information technology experts see its advantages in speeding up application's development process and in adaptability which leads us to faster response to changing business needs. Unfortunately, there are not many experiences in development of SOA solutions. One of the reasons for that lies surely in deficient and limited support of applications for planning and development of such solutions. Yet, with far more mature standards in this field, the tool's support is getting better, and with this, the SOA development solutions and their planning are becoming faster and easier. In the article, we will therefore have a look at the key advantages of SOA. and we will introduce the advantages and disadvantages of using the tools for development of SOA compliant solutions, based on experience s gained by the development of SOA prototype.
Keywords: BPEL; orkestracija; povezljivost; spletne storitve; storitveno orientirana arhitektura; WS-I